A simplified model for seismic safety assessment of reinforced concrete buildings: framework and application to a 3-storey plan-irregular moment resisting frame. (1st January 2022) - Blasone, Valentina; Basaglia, Alberto; De Risi, Raffaele; De Luca, Flavia; Spacone, Enrico
Highlights: Simplified building model for seismic assessment using dynamic analyses. Model suitable for non-shear-type buildings as it accounts for beams flexibility. Torsional behaviour of irregular buildings accurately captured. Remarkable reduction of computational time. Validation on a 3D irregular reinforced concrete moment resisting frame building. Abstract: Seismic safety assessments at the large-scale are of paramount importance for densely urbanised areas with non-negligible seismic hazard. The topic is gaining increasing interest, particularly in nations with a longstanding-built environment. Methods based on non-linear history analyses of simplified building models are increasingly relevant and popular. This paper proposes a simplified model for moment resisting frame reinforced concrete buildings, and shows its efficiency in performing non-linear history analyses on a case study building. The proposed model has three degrees of freedom per storey, two translational and one rotational around the vertical axis. The building stiffness matrix and forces are derived from the column elements. Each column is modelled with two force-inter storey drift springs, one in each horizontal direction. These springs reflect the behaviour of the columns and account also for the flexibility and strength of the connected beams through calibration of their backbone curves. A genetic algorithm is used for the calibration of the parameters for each spring. Despite the approach simplicity, the proposed modelling scheme accounts for the effects associated with irregularities both in plan and in elevation. For this reason, it represents a major improvement with respect to similar approaches for large-scale vulnerability assessments, particularly for torsionally-flexible buildings. The proposed modelling approach is applied to a three-storey plan-irregular moment resisting frame building. A refined model is used as benchmark to show how the proposed approach can reproduce the main non-linear characteristics of the case study building subjected to a suite of ground motions.